If a + b + c = 0 that means a + b = - c b + c = - a a + C = -b (1 / (a+b)(b+c)) + (1 / (b+c)(c+a)) + (1 / (c+a)(a+b)) Now put the value of equation 1, 2, 3 we get => 1 / (-c × -a) + 1 / (-a × -b) + 1 / (-b × -c) => (1 / ac) + (1 / ab) + (1 / bc) = (b + c + a) / (abc) Also we know that a + b + c = 0 So => (0 / abc) = 0
If investment is not responding to change in interest rate, then which of the following is true?
In a frequency distribution the last cumulative frequency is 500. Q3 must lie in?
The costs of inflation are?
Ability to pay principle is related with?
Which of the following is a limitation of the Command and Control approach in environmental economics?
Since the 1980s, Wal-Mart stores have appeared in almost every community in America. Wal-Mart buys its goods in large quantities and, therefore, at chea...
Calculate NNPfc from the following data:
(in Rs crores)